PENGARUH PEMBERDAYAAN PEREMPUAN TERHADAP EFEKTIVITAS PROGRAM P2WKSS KABUPATEN SUMEDANG - Anne Friday Safaria; Ririn Rosmalia (Journal Of Regional Public Administration (JRPA), 2021)
Through this theory, it will be known the causes that are easy and difficult to seek to empower women with the aim of supporting community welfare, the impact is felt limited to the aspects of knowledge of the program, the activities that are followed, the level of participation stories and program benefits. The activeness of women in various fields of life is generally determined and influenced by different backgrounds and similarities in explaining women through structural functional theory, power and status theory, non-verbal communication theory, rape-prone and rape-free theory, and division of labor theory. It also explains all activities that have been carried out and the level of achievement, the level during the implementation of the women's empowerment program. The research objectives are: 1. to know and study all activities carried out in the women's empowerment program at the Social Service 2. to find out and study the impact of implementing women's empowerment programs on the community0. The results showed that various activities were related to community welfare, especially for women who already had families. This women's empowerment program, among others, is given to understand the important role of women in leading to a healthy family. The influence of this women's empowerment program is quite large. This can be seen from the capacity and capacity of the community which is getting bigger in developing themselves. In addition, public awareness also strengthens the importance of women's roles.